A software platform for the multi-objective early-stage design of automotive assembly lines. Issue 3 (2015) - Colledani, M.; Franchini, F.; Micchetti, F.; Ratti, A.; Taurisano, A.
Abstract: The early-stage design of automotive assembly lines is a critical, multi-objective task. This design process is typically carried out in industry by continuous interactions between the process design and the simulation and systems engineering departments, resulting in a time consuming and cost-ineffective procedure. This paper presents a novel approach and a software platform to support the early stage design of hybrid assembly lines including multiple assembly technologies, such as Resistance Spot Welding (RSW) and Remote Laser Welding (RLW). This platform relies on the integration of an Assembly Layout and Process Estimator and a Configuration Optimization, based on analytical performance evaluation models. With the platform, it is possible to reduce drastically the overall cost and time required by the design procedure. A real door assembly line in the automotive industry shows the effectiveness of the proposed approach in industrial settings, analyzed within the EU FP7 funded project RLW Navigator